A QUESTÃO DO TIMBÓ E CANOINHAS: DISCURSOS E REPRESENTAÇÕES NA IMPRENSA DO PARANÁ E SANTA CATARINA (1900-1908) - Muchalovski, Eloi Giovane (2018)
This dissertation aims to analyze the discourse of the newspapers República, O Dia and Gazeta de Joinville from Santa Catarina and A República, A Notícia and Diário da Tarde from Paraná, regarding cases of violence that occurred in the valleys of the rivers Timbó and Paciência between 1900 and 1908. These cases, related to issue of delimitation and commonly reported by the press as A questão do Timbó and/or A questão de Canoinhas were the subject of heated political debate and produced several representations that refer to an imaginary of violence, which has influenced governmental and military actions in the plateau of Contestado. The historiography of “sertanejo” movement has not yet sufficiently addressed the subject. When it was done, highlighted the intensification of tensions in the region between 1905 and 1906, specifically the outrages of Colonel Demetrio Ramos and the consequent mobilization of police forces in that territory, resulting in federal military intervention in the villages of Vila Nova do Timbó and Canoinhas, which were the epicenter of events. Most of the historiographical works reproduced the reports of the military officers who participated in the Army campaign during the Contestado War, giving greater support to the claims of the newspapers from Paraná. As it turned out, the journalistic media strongly emphasized these conflicts and produced important sources for History researches. Therefore, with the methodological use of Discourse Analysis, exploring the journalistic documents, problematizing the discursive category of the region in a temporal period in which the construction of this notion, as political-administrative delimitation, was not defined. Statements on cases of assaults, arrests and murders were involved in intense relations of political and journalistic power imposed a discursively violent label to the valleys of Timbó and Paciência, perpetuated in the historiography.